2023
DOI: 10.4049/jimmunol.2200249
|View full text |Cite
|
Sign up to set email alerts
|

CXCL16 Promotes Ly6Chigh Monocyte Infiltration and Impairs Heart Function after Acute Myocardial Infarction

Abstract: High CXCL16 levels during acute cardiovascular events increase long-term mortality. However, the mechanistic role of CXCL16 in myocardial infarction (MI) is unknown. Here we investigated the role of CXCL16 in mice with MI injury. CXCL16 deficiency increased the survival of mice after MI injury, and inactivation of CXCL16 resulted in improved cardiac function and decreased infarct size. Hearts from CXCL16 inactive mice exhibited decreased infiltration of Ly6Chigh monocytes. In addition, CXCL16 promoted the macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Also, consistent with studies performed at later times post lens wounding, we found that pro-inflammatory cytokine genes are induced within 1 h post lens wounding, which at this early time included the chemokine CCL4, also known as macrophage inflammatory protein. CCL4 functions as a chemoattractant that attracts immune cells and induces their migration from the vasculature to peripheral tissues [64]. Our findings also showed a significant increase in the expression of many cytokine receptors.…”
Section: Discussionsupporting
confidence: 60%
“…Also, consistent with studies performed at later times post lens wounding, we found that pro-inflammatory cytokine genes are induced within 1 h post lens wounding, which at this early time included the chemokine CCL4, also known as macrophage inflammatory protein. CCL4 functions as a chemoattractant that attracts immune cells and induces their migration from the vasculature to peripheral tissues [64]. Our findings also showed a significant increase in the expression of many cytokine receptors.…”
Section: Discussionsupporting
confidence: 60%
“…These findings suggest that other chemokines might contribute to the recruitment of monocytes to the cortical scar in the chronic phase of HIE. Of the chemokines that exhibited chronically elevated levels in both the ipsilateral cortex and hippocampus, at least two are known to participate in monocyte recruitment to damaged tissues or tumors: CCL3 and CXCL16 (Allaoui et al, 2016;Shi & Pamer, 2011;Zhang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that other chemokines might contribute to the recruitment of monocytes to the cortical scar in the chronic phase of HIE. Of the chemokines that exhibited chronically elevated levels in both the ipsilateral cortex and hippocampus, at least two are known to participate in monocyte recruitment to damaged tissues or tumors: CCL3 and CXCL16 (Allaoui et al, 2016; Shi & Pamer, 2011; Zhang et al, 2023). In addition, CXCL16 can induce an anti‐inflammatory phenotype in microglia/macrophages (Lepore et al, 2018), and transmembrane CXCL16 can act as a scavenger receptor in myeloid cells (Wuttge et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, research has indicated that the recruitment of certain monocyte subtypes within cardiac tissue can exacerbate myocardial damage, casting uncertainty on whether monocytes foster cardiac function recovery or exacerbate injury following cardiac trauma. 94 , 95 Nevertheless, this tendency of accumulation within damaged tissues remains a subject of considerable interest. Additionally, platelet membrane surface protein P-selectin can engage with monocyte surface protein PSGL1, while platelet membrane protein GPIb binds to Macrophage receptor 1 (MAC1), thus stabilizing intercellular adhesion.…”
Section: The Regulation Of Nanoscale Modified Msc-sev In Mi/rimentioning
confidence: 99%